A model for carbonatite hosted REE mineralisation - the Mianning-Dechang REE belt, Western Sichuan Province, China - Xie, Y.; Li, Y.; Hou, Z.; Cooke, D.; Danyushevsky, L.; Dominy, Simon; Shuping, Y. (2015)
The Mianning-Dechang (MD) REE belt of Sichuan, China is one of the most important REE belt in China, which includes Maoniuping, the third largest REE deposit in the world and a series of large to small REE deposits. Mineralization styles varied across the belt, as well as within different parts of the same deposit. Styles include vein-stockworks, pegmatites, breccias and disseminated REE mineralization. Based on geological, geochemical and inclusion studies, this paper proposes a new model for carbonatite hosted REE mineralization. The results show that ore-forming fluid is derived from carbonatite magma, which has high temperature, pressure and density, and is characterized by high K, Na, Ca, Sr, Ba, REE and SO4 contents. The supercritical ore fluid underwent a distinctive evolution path including phase separation, exolution of sulfate melt and unmixing between aqueous fluid and liquid CO2. Rapid geochemical evolution of a dense carbonatite fluid causes REE mineralization and associated alteration to occur within or proximal to the source carbonatite. Veins, pegmatites and carbonatite comprise a continuum of mineralization styles. Veins occur in the outer zone of the upper levels of the deposit. Pegmatites occur in the inner zone of upper levels, whereas disseminated REE ore occurs at the base of the carbonatite. High water solubility in the carbonatite magma and low water, high REE in the exsolved ore-forming fluids, imply that a giant carbonatite body and deep magma chamber are not necessary for the formation of giant REE deposits.